Impact of Amazon land use on the community of soil fungi (Scientia Agricola, 2013)
Considered as one of the most biodiverse biomes, the Amazon has a featured role in the discovery of new species of plants, animals and microorganisms, which may be important for the functionality of different ecosystems. However, studies on the impacts resulted from changes in the Amazon land use on microbial communities and their functions are still limited. In this context, the soil fungal diversity can act as an important indicator of environmental stress caused by land use of the Amazon. This study describes changes in soil fungal communities caused by different systems of land use (primary forest, secondary forest, agroforestry, agriculture and pasture). Communities were observed in each of the areas using denaturing gradient gel electrophoresis (DGGE) of 18S rRNA gene combined with the non-metric multidimensional scaling (NMDS). Unique bands indicated the dominance of particular fungal groups in each of the specific treatments, mainly in areas converted to pasture, which differed greatly from samples of other systems of land use (SLU). The analysis of partial sequence of the 18S rRNA gene of fungi in soils under primary forest, agriculture and pasture showed differences (p = 0.001), evidencing the fungal community response to such changes. Most abundant phyla were the Zygomycota in the soil under primary forest and agricultural land, and Basidiomycota in the soil under pasture. The results show that the Amazon soil is an ecosystem susceptible to environmental changes in regarding the fungi community inhabiting this niche.